Transformations In Youth Economic Thinking Under The Influence Of Global Information Flows - Khoshimov Hakimjon Abduqaxxor Ugli (International Scientific and Current Research Conferences, 2025)
In the era of globalization, the structure and content of youth economic thinking are undergoing profound transformation under the influence of global information flows. This article examines the philosophical and socio-economic foundations of these transformations, emphasizing how digital media, transnational economic narratives, and information capitalism reshape the cognitive, value-based, and behavioral dimensions of young people’s economic consciousness. The research highlights that global informational connectivity has created a hybrid space in which national and transnational economic ideas interact, forming new patterns of consumer behavior, entrepreneurial motivation, and financial rationality. By analyzing comparative data from developed and developing societies, the study identifies both integrative and disintegrative tendencies: while global digitalization contributes to broader access to economic knowledge, it simultaneously erodes traditional economic identities rooted in local cultural context.